Mekanisasi Manusia dan Personifikasi Teknologi Menuju Keseimbangan - Eka Budianta (Antropologi Indonesia, 1999)
The author begins his observation from a linguistic phenomenon in Bahasa Indonesia that indicates swapped roles and positions between machineries and workers. Many tools including vehicles and are treated as human beings. On the other hand, a lot more cases show that workers are treated as a part of technology, if not as the machine themselves. According to the author this happens simply because workers do not have their own paradigm. Workers in Indonesia, particularly in Java, think the way their employers do. Workers easily understand, and even support any sort of management decree or decision regarding their wages and economic benefit during the Asian financial crisis. The real human resources building, however, will never be achieved unless the workers can develop a perspective that is free from the penetration of the establishment and their high-tech machineries.